Pemenuhan Hak Anak Atas Dokumen Akta Kelahiran Di Kabupaten Nunukan Provinsi Kalimantan Utara - Mawardi Khairi; Inggit Akim (Fakultas Hukum Universitas Mataram, 2018)
Ownership residence documents are very important to all communities as proof of recognition by the state. The residence documents such as birth certificate is one of the rights of children that must be met by the government as a form of legal protection or recognition of citizenship. Based on the results of research shows that fulfilling the children's right to document a birth certificate in cabs Nunukan to do the service, the act of the scope of the public directly entered by local governments through measures in the form of direct services birth certificate in the office The Department of Population and Civil Registration, generally carried out (deed scope), held a collection directly children who have no birth certificates with the help of local authorities under the district, village, neighborhood / village up to the neighborhood and have signed a cooperation agreement (MOU ) to establish with competent authorities such as the Ministry of Education and Culture of Nunukan, Nunukan Nunukan hospitals and IBI Branch since 2016 as an attempt to optimize the fulfillment of the child's rights to legal documents such as birth certificate that all benefits are free. The results of this study are expected to contribute to training in specific areas of law and human rights as well as to refer both central and local governments into making future policy, especially in the area of population administration.